Writing news features - Masterton, Murray. (2008)
After the struggles and justifications of interpretive and investigative journalism, discussing die writing of newspaper features seems deceptively easy. Too many reporters who are asked to expand tiieir news reports into feature material look on it just that way. which is why feature writing seems to be confined to a few people on every staff I'm sure it is the same way around the world.What is a feature and in what way does it differ from an everyday news item?To begin with, a feature story is usually much longer. There are long news stories, and there are serials which run for days or weeks, or even months, but each days appearance is a news report, not a feature. The best comparison I know is one that comes from broadcasting, comparing news reports with current affairs reports, which are in many ways the same as short features.